1994
DOI: 10.1002/macp.1994.021950233
|View full text |Cite
|
Sign up to set email alerts
|

The system methylcyclohexane/polystyrene. Experimental critical curves, cloud‐point and spinodal isopleths, and their description with a semi‐phenomenological treatment

Abstract: Cloud-point and spinodal pressures up to 900 bar were investigated for the system methylcyclohexane/polystyrene using a pressure-pulse-induced scattering technique based on the theory of Debye. The molar-mass range of the polymer samples is 9-50 kg/mol. The values determined isothermally in a large concentration range for a polymer sample with weight-average molar mass Hw = 17,5 kg/mol lead to isopleths which allow the construction of phase diagrams displaying cloud-point and spinodal curves (in terms of tempe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

1994
1994
2019
2019

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 23 publications
(10 citation statements)
references
References 42 publications
0
10
0
Order By: Relevance
“…A distinct improvement of the quality of the calculated CPC is not reached by changing the concentration dependence of the g function from the linear type of b g to the squared type of c g . The closed form of the g function d g , which has been introduced by Koningsveld and Kleintjens, leads to a reasonable locus of the calculated CPC . But the shape of the calculated curve, which is the dotted curve in Figure , also deviates from the very flat one of the experimental CPC.…”
Section: Resultsmentioning
confidence: 81%
See 1 more Smart Citation
“…A distinct improvement of the quality of the calculated CPC is not reached by changing the concentration dependence of the g function from the linear type of b g to the squared type of c g . The closed form of the g function d g , which has been introduced by Koningsveld and Kleintjens, leads to a reasonable locus of the calculated CPC . But the shape of the calculated curve, which is the dotted curve in Figure , also deviates from the very flat one of the experimental CPC.…”
Section: Resultsmentioning
confidence: 81%
“…For a Gibbs free enthalpy of mixing according to eq 3 it follows that and where γ represents the phase indices ‘ or ‘‘ and i = 2, 3, ..., N and r̄ n is the number average of r i . The parameter χ 1 γ represents the interaction parameter of the solvent in the phase γ, and the parameter χ p γ represents the same of the polymer. ,,, They are defined by and By the use of the distribution coefficient σ, it follows that ,, with which reflects the fractionation of a polymer component i enriched either in the dilute or in the concentrated coexisting phase. By a summation over all polymer species i , eq 7a leads to the polymer concentration φ p ‘‘: Assuming a certain mmd in the original polymer sample and assuming an appropriate thermodynamic framework, a stepwise iteration may be performed that should give the CPC and the shadow curve of the system.…”
Section: Introductionmentioning
confidence: 99%
“…PS/MCH solutions form examples of at least the lower part of the reentrant diagram illustrated in Figure 4. Previous observations of the demixing diagram for PS/ MCH at modestly elevated pressures have been reported by Vanhee et al 44 (0.1 < P/MPa < 90), Van Hook et al, 4,9,10 Enders and de Loos, 45 Hosokawa, Nakata, and Dobashi, 46 and Wells et al 47 and correlated by Imre and Van Hook. 6 The earlier work establishes the existence of a lower hypercritical temperature (T hyp L ) 305 K, 55 MPa, at M w (PS) ) 3 × 10 4 ), and points to the existence of a lower hypercritical pressure at P < 0, but not too deep (P hyp L ) ∼34 010 K, ∼-15 ( 3 MPa at M w (PS) ) 3 × 10 4 , dropping off to P hyp L ) ∼360 ( 10 K, ∼-10 ( 3 MPa, at M w (PS) ) 2 × 10 6 ).…”
Section: Dls Correlation Radii In the (P T ψ C ) Projection For Ps/mc...mentioning
confidence: 72%
“…Although in most cases increased pressure improves SQ, that behavior is not universal. Others have reported that increasing the pressure improves SQ by transforming a θ solvent into a good solvent17–21 or a poor solvent into a θ solvent 22, 23. The results at room temperature show that SQ improves with pressure ( d SQ/ dP > 0) in the good (PS/toluene and PS/chloroform) and poor (PS/MCH) solvents studied.…”
Section: Discussionmentioning
confidence: 86%
“…Others have employed liquid–liquid phase equilibria to determine dT UCST / dP , another measure of SQ. In this way, several groups have reported that increasing pressure improves SQ by transforming a θ solvent into a good solvent17–21 or a poor solvent into a θ solvent 22, 23. Although in most cases increased pressure does improve SQ, that behavior is not universal.…”
Section: Discussionmentioning
confidence: 99%